Integrating Ecotheology into Organizational Dynamics of Islamic Education: A Conceptual Model Based on Systematic Review - trian hermawan; Samsul Hadi; Subandi; Encep Syarifudin (Journal of Educational Management Research, 2026)
This study aims to develop a conceptual model of organizational dynamics for environmentally oriented Islamic educational institutions grounded in Islamic ecotheology. Using a Systematic Literature Review (SLR), publications from 2010 to 2025 were examined across major academic databases, including Scopus, Web of Science, ScienceDirect, SpringerLink, Taylor & Francis, SAGE, DOAJ, SINTA, GARUDA, and Moraref. The review followed the PRISMA 2020 framework and resulted in the inclusion of 32 eligible articles. The findings reveal that ecological transformation within Islamic educational institutions relies on the coherence of four interrelated elements: the internalization of ecotheological values within institutional vision and strategy, prophetic-transformational leadership that drives organizational change, structural and policy frameworks that institutionalize sustainability principles, and a participatory organizational culture that cultivates an ecological habitus among institutional members. These elements interact dynamically to shape sustainable institutional practices. The proposed conceptual model contributes theoretically to the discourse on sustainable Islamic educational management and provides practical guidance for pesantren, madrasahs, and Islamic higher education institutions in their transition toward becoming Islamic Green Institutions.